Profil Protein pada Organ Tikus (Rattus norvegicus) Model Diabetes Melitus Tipe 2 (DMT2) - Yohanes Bare; Fatchiyah Fatchiyah (Universitas Islam Negeri Mataram, 2018)
Type 2 diabetes mellitus (T2DM) caused by resistance to insulin. Resistance insulin leads to hyperglycaemia. Prolong hyperglycaemia caused damaged organ and complication such as nephropathy (kidney), liver and cardiovascular diseases. Meanwhile, resistance insulin inhibits protein metabolism. This study focused on investigated of profile protein organ kidney, liver and heart in T2DM rat animal model. This research was used rats group T2DM (DM) and normal rats as a control (C). We isolated Protein from tissues and SDS-Page to investigated profile protein. This result we found has different profile protein in T2DM rats (DM) compared with control rats (C). Heart control (HC we found 5 bands protein, meanwhile organ HDM found 8 bands protein. In organ LiC we found 8 bands protein, besides organ LiDM 6 bands protein. Kideny control (KC) we found 7 bands protein, meanwhile organ KDM only 6 bands protein. This study concluded has different profile protein in rats group T2DM (DM) and rats control group (C).